2023
DOI: 10.1192/j.eurpsy.2023.22
|View full text |Cite
|
Sign up to set email alerts
|

The Goldwater Rule at 50 and its relevance in Europe: Examining the positions of National Psychiatric Association Members of the European Psychiatric Association

Abstract: This peer-reviewed article has been accepted for publication but not yet copyedited or typeset, and so may be subject to change during the production process. The article is considered published and may be cited using its DOI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The topic is extremely important, as psychiatrists' involvement with the media could be against the principles of accuracy, dignity, but also beneficence, non-maleficence, and respect for the person, given the potentially harmful effects on the individual who is the object of the public discussion [24]. The key role of international psychiatric associations' codes of ethics becomes evident in the light of a recent study that systematically reviewed the topic of psychiatrists' involvement with the media coverage of mental health issues in different European countries and reported that a sizeable proportion of national psychiatric association did not offer guidance on this specific topic [25]. Therefore, given the importance of communication, especially in the digital era [26], both the EPA and WPA codes might benefit from a revision of the sections relevant to this topic.…”
Section: Discussionmentioning
confidence: 99%
“…The topic is extremely important, as psychiatrists' involvement with the media could be against the principles of accuracy, dignity, but also beneficence, non-maleficence, and respect for the person, given the potentially harmful effects on the individual who is the object of the public discussion [24]. The key role of international psychiatric associations' codes of ethics becomes evident in the light of a recent study that systematically reviewed the topic of psychiatrists' involvement with the media coverage of mental health issues in different European countries and reported that a sizeable proportion of national psychiatric association did not offer guidance on this specific topic [25]. Therefore, given the importance of communication, especially in the digital era [26], both the EPA and WPA codes might benefit from a revision of the sections relevant to this topic.…”
Section: Discussionmentioning
confidence: 99%
“… 6 During the 2016 contest, such discussions became increasingly animated when psychiatrists provoked ethical controversies through public views on Mr. Trump. 1 , 5 , 7 Later, in the 2020 campaign, speculation abounded about Mr. Biden, as exemplified when Mr. Trump publicised his own results from the Montreal Cognitive Assessment (a screening tool for cognitive decline and dementia). 3…”
mentioning
confidence: 99%
“…Nevertheless, critics contend that the Goldwater Rule restricts free expression, enabling experts from allied fields (e.g., psychologists or neurologists), non-US psychiatrists, or laypeople to disproportionately sway public agendas. 7 Others highlight a lack of enforcement mechanisms and the anachronisms of the Goldwater Rule for modern online platforms. Both may require nuanced consideration given the ethical implications of digitally-generated disinformation.…”
mentioning
confidence: 99%
See 1 more Smart Citation